Sacred Space in England, 1560–1640: The View from the Pew - Marsh, Christopher (The journal of ecclesiastical history, 2002)
This article employs evidence relating to church seating between 1560 and 1640 in order to argue that English people experienced the interior of their parish church as a setting of profound significance. It seeks to augment the rather secular interpretative framework within which social and economic historians have tended to consider the importance of church seating. Such seating mattered to people not only because of their preoccupation with social precedence during a period of economic strain, but because of its stirring and symbolic location. Church seating also deserves to be interpreted as evidence of popular attachment to the church, rather than almost exclusively as an instrument of social control deployed by parochial leaders. Much of the surviving documentation relates to the misdemeanours of a conspicuous minority, but it is also possible to examine the sources for what they reveal of the arguably more positive attitudes of the ever elusive majority.